2017
DOI: 10.3390/cryst7060154
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Characterization of Tetraphenylphosphonium Bromide Crystal

Abstract: Multiple-phenyl phosphorous compounds are a group of chemical materials that have been used as reactants, pharmaceutical intermediates, extractants, and catalysts in organic synthetic reactions. However, the crystal growth of bulk crystals of multiple-phenyl phosphorous compounds, which may expand their applications in photonics technology, have been largely overlooked. In this article, the crystal growth of tetraphenylphosphonium bromide (TPPB) has been studied in organic solvents and water. The crystal struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…24 The structure of TppBr fibers is identical with that of its bulk crystal obtained by the spontaneous nucleation and growth in water solution (Figure 2a). 20 There are two molecules of crystal water in the lattice. The XRD spectrum of TppBr fibers without grinding shows that the strong diffractions come from (101), (103), and (100) crystal faces (see Figure 2b).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…24 The structure of TppBr fibers is identical with that of its bulk crystal obtained by the spontaneous nucleation and growth in water solution (Figure 2a). 20 There are two molecules of crystal water in the lattice. The XRD spectrum of TppBr fibers without grinding shows that the strong diffractions come from (101), (103), and (100) crystal faces (see Figure 2b).…”
mentioning
confidence: 99%
“…Recently, we found that TppBr could exhibit different crystallization features under the varied growth conditions. Bulk crystals of TppBr could grow by spontaneous nucleation and slow evaporation of its aqueous or ethanol solution . However, as the hot water solution of TppBr was dropped on a glass slide, rapidly evaporated, and cooled, TppBr may nucleate at the edge and surface of the droplet and finally self-assemble into one-dimensional fiber crystals of several millimeters in length in a few minutes.…”
mentioning
confidence: 99%
See 1 more Smart Citation